2022
DOI: 10.21203/rs.3.rs-2398112/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insecticide resistance status of Aedes aegypti in Southern and Northern Ghana

Abstract: Background Outbreaks of Aedes-borne arboviral diseases are becoming rampant in Africa. In Ghana, there is no organized arboviral control programme with interventions restricted to mitigate outbreaks. Insecticide application is a crucial part of outbreak responses and future preventative control measures. Thus, knowledge of the resistance status and underlying mechanisms of Aedes populations is required to ensure optimal insecticide choices. The present study assessed the insecticide resistance status of Aedes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…This might be due to the indirect impact of the use of insecticides for public health vector control such as the use of Long-Lasting Insecticidal Nets (LLINs) and IRS, as well as pesticide in agriculture (11,42,43). This nding is similar to that reported in a study conducted in Ghana (Abdulai et al, 2023). Whereas Aedes mosquitoes collected from Pagaza and Kpalsogu showed suspected resistance to Permethrin, samples from Larabanga were found to be susceptible to Permethrin.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This might be due to the indirect impact of the use of insecticides for public health vector control such as the use of Long-Lasting Insecticidal Nets (LLINs) and IRS, as well as pesticide in agriculture (11,42,43). This nding is similar to that reported in a study conducted in Ghana (Abdulai et al, 2023). Whereas Aedes mosquitoes collected from Pagaza and Kpalsogu showed suspected resistance to Permethrin, samples from Larabanga were found to be susceptible to Permethrin.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, other studies in Ghana have found high frequencies of V1016I and F1534C kdr mutations in both pyrethroid-susceptible and resistant Aedes mosquitoes collected in Ghana (9,21). This suggests that other resistance mechanism such as metabolic resistance may be involved in insecticide resistance of Aedes aegypti populations in Ghana.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations